Meningkatkan Hasil Belajar Pendidikan Agama Katolik dengan Metode Problem Based Learning (PBL) pada Materi Aku Mengembangkan Diri Bersama Orang Lain Kelas IV Fase B pada SD Negeri 15 Buntumauli - Monika Mestika Simamora (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to improve the learning outcomes of Catholic Religious Education by implementing the Problem-Based Learning (PBL) method in the lesson "I Develop Myself Together with Others" for fourth-grade students in Phase B at SD Negeri 15 Buntumauli. The PBL method is a student-centered approach that emphasizes problem-solving of real-life issues relevant to the subject matter. This method promotes critical thinking, creativity, and collaboration among students, which are essential skills in modern education. Through this method, students are encouraged to be more active in their learning process, exploring problems, discussing solutions, and working together in groups to solve them. The research was conducted over two cycles, with each cycle consisting of planning, implementation, observation, and reflection. Data were collected through observation, written tests, and documentation. The focus of the observation was on student activity during the learning process, their participation in discussions, and how well they were able to develop problem-solving strategies in group work. Learning tests were administered to measure the students' understanding of the material before and after applying the PBL method. The results showed a significant increase in students' learning outcomes after the introduction of the PBL method. There was a notable improvement in their understanding of the material, particularly in relation to personal development and social interaction. Students were more engaged and motivated during the lessons, displaying greater responsibility and independence in their learning. They also demonstrated stronger teamwork and communication skills. Based on these findings, it can be concluded that the PBL method is an effective tool for enhancing the quality of Catholic Religious Education, specifically in topics related to self-development and cooperation with others. This method encourages students to think critically, solve problems creatively, and collaborate with their peers.